Task-Technology Fit (TTF) dan Unified Theory of Acceptance and Use of Technology (UTAUT): Analisis Model Penerimaan Teknologi di Perguruan Tinggi - Fitrianto Puja Kesuma; Dedy Syamsuar (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
Information technology has been widely used in universities as a medium for related academic information. However, students in this case prefer to use social media to find information compared to looking for academic information that has been provided by the university. Students are still not active in utilizing academic information systems. Some services are still not fully utilized by students, such as: class schedules, study reports, academic calendars. In this study, the combination of the TTF and UTAUT models was used in analyzing the acceptance of the academic system in universities. The distribution of questionnaires in this study using google form and involving three universities that are used as respondents. From the research results, there are several variables used that have not significantly affect based on the perceptions of each respondent in three universities. From these results, it can be concluded that there are variables that consistently have a significantly affect, namely task characteristics towards task-technology fit, technology characteristics towards task-technology fit, task-technology fit towards performance expectancy, and effort expectancy towards performance expectancy.